Atherosclerosis and Vascular Imaging 2016 - Michael Henein (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Cardiovascular disease is the main cause of death in the West, and vascular disease is the most common cardiovascular clinical problem. The disease results in serious morbidity and mortality, and carries economic cost implications. While conventional risk factors are well established, and their biomarkers regularly monitored, patients may continue to suffer subclinical active disease, even in the absence of risk factors, until they present with sudden cardiac death or stroke. Early disease detection using direct imaging has shown to be more accurate in identifying vulnerable patients and unstable plaques than conventional risk factors. This IJMS Special Issue deals with the current opinion concerning the state-of-the-art imaging technologies available for clinical applications, and their unique value over the sole use of conventional risk factor analysis, in identifying vulnerable patients, recommending aggressive treatments, prognosticating, and in assessing related nutritional and environmental issues. This Special Issue is the continuation of our 2015 Special Issue "Atherosclerosis and Vascular Imaging"